2013
DOI: 10.1007/s00347-012-2710-0
|View full text |Cite
|
Sign up to set email alerts
|

Moderne Filtrationschirurgie

Abstract: Preoperative treatment with steroids and nonsteroidal anti-inflammatory drugs increases the success of filtration surgery. Surgery with the patient under subconjunctival anesthesia is safe. Intraoperative application of mitomycin C is state of the art and enhances success rates. Perioperative use of bevacizumab seems to attenuate postoperative fibrosis. Postoperative hypotension is avoided by stable fixation of the scleral flap followed by stepwise controlled suturelysis or release. Transconjunctival flap sutu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The currently used preoperative preparation in Mainz and other centres [ 12 ] has several potential disadvantages [ 13 15 ] We therefore sought an alternative preoperative treatment that would be better tolerated by patients in terms of safety and quality of life, that would require less visits to the ophthalmologist and general practitioner and would therefore be cheaper, and is that would be equally effective in reducing IOP three and six months after trabeculectomy. No treatment guidelines yet exist for the pretreatment prior to trabeculectomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The currently used preoperative preparation in Mainz and other centres [ 12 ] has several potential disadvantages [ 13 15 ] We therefore sought an alternative preoperative treatment that would be better tolerated by patients in terms of safety and quality of life, that would require less visits to the ophthalmologist and general practitioner and would therefore be cheaper, and is that would be equally effective in reducing IOP three and six months after trabeculectomy. No treatment guidelines yet exist for the pretreatment prior to trabeculectomy.…”
Section: Introductionmentioning
confidence: 99%
“…No treatment guidelines yet exist for the pretreatment prior to trabeculectomy. Following recommendations by Klink et al [ 12 ], we decided to use preservative-free ß-blockers and/ or carbonic anhydrase inhibitors as a comparator.…”
Section: Introductionmentioning
confidence: 99%
“… 56 A recent review article on ‘modern filtration surgery’ concluded that ‘subconjunctival anesthesia is safe’. 59 …”
Section: Preoperative Preparation: Does the Patient Really Need A Tramentioning
confidence: 99%
“… 1 Thus, current evidence indicates that anesthesia technique has no major effect on postoperative complication rate. 2 59 …”
Section: Preoperative Preparation: Does the Patient Really Need A Tramentioning
confidence: 99%
See 1 more Smart Citation